Amino acids for Diels-Alder reactions in living cells - Plass, Tilman; Milles, Sigrid; Köhler, Christine; Szymański, Jędrzej; Müller, Rainer Wolfgang; Schultz, Carsten; Lemke, Edward A. (Angewandte Chemie. International edition, 2012)
Under tension: A set of genetically encoded unnatural amino acids can be used for biocompatible site-specific labeling of proteins with fluorogenic dyes. The new compounds have norbornene and trans-cyclooctene units that react with tetrazine derivatives in an inverse-electron-demand Diels-Alder cycloaddition (left in picture). The technique offers fast labeling that is orthogonal to labeling through azide-cyclooctyne click reaction (right).